The family Pyronemataceae (Pezizales, Ascomycota) in the Republic of Macedonia - Kajevska, Iskra; Rusevska, Katerina; Karadelev, Mitko (Macedonian Journal of Ecology and Environment, 2013)
This is the first attempt of systematic research into Pyronemataceae family (Pezizales, Ascomycota) in the Republic of Macedonia. The aim of this paper was to present all available data (species diversity, brief ecology and distribution) on Pyronemataceae fungi in the country. Compiled species list includes data from existing literature (12 publications), 128 data from the MACFUNGI database, 110 exsiccates from the Macedonian Collection of Fungi (MCF) and our own field research trips, observations and identification. A total of 28 species belonging to 12 genera have been recorded. The highest number of species belongs to the genera Otidea (7), Scutellinia (4) and Genea (3 species). The most frequent species are Aleuria aurantia, Humaria hemisphaerica and Scutellinia scutellata. The species Genea fragrans, G. hispidula, G. verrucosa, Geopora arenicola and G. sumneriana are hypogeous fungi. Five genera (Anthracobia, Cheilymenia, Melastiza, Trichophaea, Trichophaeopsis) and 14 species are reported as new for the mycobiota of Macedonia.